2020
DOI: 10.1101/2020.02.28.20028720
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A new content-qualified antenatal care coverage indicator: development and validation of a score using national health surveys

Abstract: Background: Good quality antenatal care (ANC) helps reducing adverse maternal and newborn outcomes, especially in low and middle-income countries (LMICs). Most of the currently used ANC indicators only measure contact with services. We aimed to create and validate a new indicator measured as a score, considering both contact and content, that can be used for monitoring. Methods: We used data from national surveys conducted in LMICs. Information on ANC was used to build an adequacy score (ANCq) that would be a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Women with 4 points in the ANCq score mostly had less than four ANC visits, tetanus immunization, a skilled provider, blood pressure measured, and nothing else. 8 In terms of absolute wealth inequalities, measured by the SII, we observed that countries with higher mean ANCq presented lower inequalities, generally. Most of them are uppermiddle income countries.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Women with 4 points in the ANCq score mostly had less than four ANC visits, tetanus immunization, a skilled provider, blood pressure measured, and nothing else. 8 In terms of absolute wealth inequalities, measured by the SII, we observed that countries with higher mean ANCq presented lower inequalities, generally. Most of them are uppermiddle income countries.…”
Section: Discussionmentioning
confidence: 63%
“…Women with 4 points in the ANCq score mostly had less than four ANC visits, tetanus immunization, a skilled provider, blood pressure measured, and nothing else. 8…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ANCq -content-quali ed ANC coverage indicator [8] -was proposed as a new indicator that combines a set of key aspects of contact with services and content of care. In contrast to most of the existing ANC indicators, ANCq is calculated as a score giving an idea of level of adequacy, and also considering all pregnant woman in need of ANC and not only those who had at least one visit.…”
Section: Introductionmentioning
confidence: 99%